INFRARED DRYING IN TECHNOLOGY OF DRIED FRUIT FROM MACROCARPOUS PURPLE PRÚNUS CERASÍFERA - Nina Vadimovna Alexeyeva (Алматы технологиялық университетінің хабаршысы, 2022)
Peculiarities of infrared drying in the technology of production of dried fruit from large Prúnus cerasífera are described in the paper. Infrared drying of fruits is carried out in one stage. All the necessary technological parameters at each stage of the technology are given. As a result, useful dried fruit with an improved appearance is obtained. By its chemical composition the fruit is similar to plum applied for producing prunes. The analysis of chemical composition of plums and macrocarpous purple Prúnus cerasífera is given. The data substantiate the relevancy for production of dried fruit from Prúnus cerasífera. Then the developed technology of dried fruit production is described.